Trends and Linkages in Schooling and Work Among Cambodian Youth : A Synthetic Panel Analysis - World Bank (World Bank, Washington, DC, 2019)
During the decades following the Khmer Rouge regime of the 1970’s and Vietnamese occupation in the 80’s, the Cambodian government focused on rebuilding what had been destroyed during that time. There was a renewed focus on the education sector: the 90’s and 2000’s saw large-scale reconstruction of schools and policies which increased access to schooling. Reports estimating schooling outcomes have found corresponding increases in schooling enrollment. To add to existing literature we analyze 11 years of nationally-representative cross-sectional data in a new way: using a cohort panel approach developed by Deaton in his 1985 paper (Deaton 1985). We construct a panel of 19 cohorts spanning birth years 1980 to 1998 and estimate their life cycle trajectories as these cohorts aged from youth into early adulthood. This approach allows us to control for contemporaneous time effects and trace out the smoothed cohort and age trends in schooling and work outcomes. We answer the question “For a given age, have schooling and work outcomes improved or declined with more recent versus older cohorts? Are there differences in improvement or decline when comparing males versus females, rural versus urban youth?” Using the variation in experiences across cohorts, we are additionally able provide evidence on how early youth experiences translate to outcomes later in life.